The Criticisms on the Orientalistsâ€™ Shubha and the Arguments on the Authenticity of the Qurâ€™an - Mustaqim, Abdul (DINIKA : Academic Journal of Islamic Studies, 2020)
This article reconsiders theÂ shubhaÂ (misgrounded conceit) proposed by the orientalists. The firstÂ shubhais about the revelation of the Qurâ€™an; the secondÂ shubhais about the differences of qiraâ€™at (recitations or readings) claimed by the orientalists as proof that the Quran is not entirely authentic for the existence of false readings. The thirdÂ shubhaÂ is about the authorship and the relationship of the Qurâ€™an with previous divine books (Tawrat and Bible) showing that the Qurâ€™an is a plagiarism work of The Prophet Muhammad or the notion of influence or borrowings from Judeo-Christian tradition. Employing the theological-historical approach, this article argues that, firstly, that the Qurâ€™an is a Divine Revelation is evident from the linguistic style in which it very often uses direct speech to Muhammad, such as â€œSay, (O Muhammad to the mankind)â€, and from the criticism posed by the Qurâ€™an to Muhammad as the recipient of the revelation. Historically, the process of the writing of the Qurâ€™an has started since the lifetime of the Prophet Muhammad and was based on reliable sources, either oral or written, supported by oaths from witnesses from the companions affirming the reliability of the existing records of the Qurâ€™an during that period. Secondly, concerning the variation of the readings, if they are transmitted inÂ mutawatir,Â they are the accepted readings, because theologically the Qurâ€™an was revealed with differences of readings ofÂ sabâ€™at ahruf,Â in which there are a lot of hikmaÂ and there is no contradiction. Finally, concerning the similarities (either the content or dictions) between the Qurâ€™an and previous divine books, the notion of plagiarism is not relevant; it suggests the consistent and reliable chains of Divine Revelation between the messengers, making they are not in contradiction to the revelation received by the Prophet Muhammad (Q.S. Al-NisaÊ¾[4]: 163-164). From the historical-philological perspective, the similarities of concepts or content between the Qurâ€™an and Bible indicate that the Qurâ€™an is in dialogue with the textual discourses found in its environment. It is reasonable because the Qurâ€™an was not revealed in a vacuum context.Â